A case study on the effect of self-assessment on EFL learners’ self-efficacy beliefs - YILMAZ VİRLAN, AYŞE (My University, 2022)
This study aimed to look into the impact of continuous self-assessment on the self-efficacy beliefs of undergraduates studying English as a foreign language (EFL). To find out if there is a change in students’ beliefs about their language proficiency perception, the research was undertaken with 102 participants at the school of foreign languages of a private university. It was designed as quasi-experimental research utilizing qualitative and quantitative research methods to collect data through a self-efficacy scale, self-assessment questionnaire, and self-reflection checklists. The control and experimental groups were administered a self-efficacy scale at the beginning and the end of the term. Throughout the term, the participants in the experimental group assessed themselves weekly through self-reflection checklists and a self-assessment questionnaire. Based on the overall results, it was found that when the students had an opportunity to identify their strengths and weaknesses during a skill-based task through self-assessment questionnaires, they had a better sense of mastery related to that task. This inevitably led to an increase in their self-efficacy beliefs in terms of four skills, namely reading, writing, listening, and speaking as well as grammar.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Yabancı Diller Eğitimi; Social Sciences and Humanities; Education; Educational Sciences; Education in Foreign Languages; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SCIENTIFIC DISCIPLINES; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; English as a foreign language; second language teaching; self-assessment; self –efficacy; self-reflection